PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BOOK DALAM PEMBELAJARAN IPS KELAS IV MATERI KERAJAAN PADA MASA HINDU DAN BUDDHA - Gusnaini, Putri; Putra, M. Jaya Adi; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The use of learning media in teaching and learning activities is a way of supporting learning activities. The use of learning media can serve as a tool to accelerate the process of understanding in teaching and learning activities in the classroom. With the existence of attractive learning media with a three-dimensional appearance like the original, it can make students more enthusiastic and also become more interested in learning to use these learning media. The average validation obtained from material experts is 87.33% with a very feasible category and 93.81% for media experts with the conclusion that it is feasible to be tested without improvement. And the average percentage for the teacher's response to the product that has been made is 87.5% in the very good category and the average percentage of the student's response is 98.5% in the very good category.Key Words : Pop-up Book Learning Media, Hindu-Buddhist Kingdom